The Enhancement of the Learning Achievement of Science in the Material of Human Organs Structure with Problem-Based Learning Method for the Fourth Graders of SD Negeri Botoputih Odd Semester in the Academic Year 2017/2018 - Ani Iinsiyah (Indonesian Journal of Biology Education, 2019)
The purpose of this research is to enhance students' ability of science subject in the material of human organs structure with the problem-based learning method for the fourth graders of elementary school. This research is conducted with the fourth graders odd semester of SD Negeri Botoputih in the Academic Year 2017/2018 as the subject. Based on the result of classroom action research on the implementation of Problem-Based Learning Model to enhance the students’ learning achievement of science subject in the material of human organs structure for the Fourth Graders of SD Negeri Botoputih Odd Semester in the Academic Year 2017/2018, it can be stated that the learning outcome of science subject in the material of human organs structure in the pre-cycle with a minimum score standard of 70 is not optimal yet. The data shows 22 students in total that there are 10 students with a percentage of 45.45% can complete and pass the minimum score standard. While 12 students with a percentage of 54.55% are failed. The cause is because of the lack of evaluation method in a science subject. The result of the first cycle shows that science subject in the material of human organs structure with a minimum score standard of 70 has not been optimal yet. The data shows 22 students in total that there are 17 students with a percentage of 77.27% can complete and pass the minimum score standard. While 5 students with a percentage of 22.73%. The result of the second cycle shows that science subject in the material of human organs structure with a minimum score standard of 70 is optimal and much better. The data shows 22 students in total that there are 22 students with a percentage of 100% can complete and pass the minimum score standard. Surely, there is nobody failed with a percentage of 0%